Estimation of Heterosis and Heterobeltiosis in Interpoblational Hybrids of Husk Tomato (Physalis ixocarpa Brot.) - Camposeco-Montejo, Neymar (2020)
The objective of the investigation was to evaluate progenitors and their crosses, and to estimate heterosis and heterobeltiosis in hybrid of husk tomato (Physalis ixocarpa Brot). The progenitors were UAN CC-S2 (1), a genotype of Physalis angulata (2), UAN CP-S2 (3), Gran Esmeralda (4), UAN CJ-S2 (5), Rendidora (6), and UAN 133- 05 (7). The crosses, plant to plant, were done under greenhouse conditions in autumn-winter of 2012; the evaluation of the crosses and the parents were done in the municipality of General Cepeda, Coahuila, Mexico, in the spring-summer of 2013, under a randomized block design with three repetitions. In yield, the best cross was 3*4, with yields of 47.19 t.ha-1, heterosis of 35.93%, and heterobeltiosis of 20.85%; however the 1*6 cross presented the highest values of heterosis and heterobeltiosis, 117.91 and 117.62% respectively; in number of fruits per plant, crosses 7*3 showed the highest values of heterosis and heterobeltiosis, 109.19 and 89.96% respectively; in terms of average fruit weight, equatorial diameter of fruit, and polar diameter of fruit, the best cross was the 3*4, that presented heterosis of 41.17, 11.40, and 12.56%, and heterobeltiosis of 37.99, 9.26, and 12.03%, respectively, although cross 1*5 values of heterosis and heterobeltiosis in average weight were 115.91 and 107.83% respectively. Among the populations studied there is genetic divergence, since they presented high values of heterosis; in addition, the maternal effects significantly influenced the variables under study, indicating the best direction of the cross.